Nikah Mut’ah - Harahap, Rindur Rodiah; Ardi, Siti Arawiyyah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Family life or living in marriage is a reasonable and healthy hope and intention of every human being in their growth and development. Marriage in the view of Islam is something noble and sacred, meaningful Worship to Allah SWT, following the Sunnah of the Prophet and carried out on the basis of sincerity, Responsibility, and following the provisions of the law that must be obeyed. A prosperous family (sakinah family) is the dream of every person who is married. At all times, efforts to realize this sakinah family continue to be made, because, a sakinah family is not formed by itself, but, must be attempted and through a long process with a long time, let alone for a marriage with a limited time (mut'ah), a family that is built on a contract that is not limited by time (daim) is also very difficult to realize a sakinah family. Differences in scholars in responding to marriage always invite controversy to become a topic that is interesting to study, controversial marriages include mut'ah marriage. In this study, namely discussing the understanding and the fuqoha differing opinions regarding the law of the permissibility of mut'ah marriage. The issue of whether mut'ah marriage is still valid or not is an object of Ijtihad study, because it is a khilafiyah issue. In accordance with the purpose of marriage in Islam in general, and Law No. 1/1974 concerning Marriage, under normal circumstances mut'ah marriage is unacceptable, but in an emergency it can certainly be considered and seen which is greater in benefits and disadvantages.